2016
DOI: 10.1177/1535370216668050
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase/protein kinase B/periostin mediated platelet-derived growth factor-induced cell proliferation and extracellular matrix production in lupus nephritis

Abstract: In the present study, the effect and mechanism of periostin on renal proliferation and extracellular matrix accumulation of lupus mice were investigated. MRL /lpr mice, known as lupus mice, were revealed to show enhanced periostin, proliferating cell nuclear antigen (PCNA), and extracellular matrix accumulation in the kidney accompanied by increased serum platelet-derived growth factor (PDGF). Again, cultured mouse mesangial cells (MMCs) were treated with PDGF, then periostin, and PCNA and secreted fibronectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Fibronectin, a ubiquitous glycoprotein of ECM that plays a role in tissue remodeling is considered as a decisive contributing factor to switch from normal wound healing to deregulated fibrosis ( Petrini et al, 2017 ). Excess fibronectin is produced from endothelial cells and fibroblasts upon stimulation of growth factors including platelet derived growth factor and TGF-β1 ( Hocevar et al, 1999 ; Zhao et al, 2017 ). Hence, the role of WFA on fibronectin was evaluated and we observed dramatic decrease in expression of fibronectin in WFA treated HFL1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin, a ubiquitous glycoprotein of ECM that plays a role in tissue remodeling is considered as a decisive contributing factor to switch from normal wound healing to deregulated fibrosis ( Petrini et al, 2017 ). Excess fibronectin is produced from endothelial cells and fibroblasts upon stimulation of growth factors including platelet derived growth factor and TGF-β1 ( Hocevar et al, 1999 ; Zhao et al, 2017 ). Hence, the role of WFA on fibronectin was evaluated and we observed dramatic decrease in expression of fibronectin in WFA treated HFL1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is critical for fibrotic progression in glomerulonephritis and is distributed widely in the mesangial matrix, glomerular, and tubular basement membranes, and Bowman's capsule. The formation of glomerular fibronectin is enhanced both in patients and mice with active LN (90, 91). We have demonstrated that anti-dsDNA IgG contributes to renal fibrosis by downregulating suppressor of cytokine signaling 1 (SOCS1) and activating Janus kinase/signal transducer and activator of transcription 1 signals, which modulate the expression of profibrotic genes, transforming growth factor beta 1 (TGF-β1), platelet-derived growth factor B, and connective tissue growth factor (92, 93).…”
Section: The Pathogenicity Of Anti-dsdna Antibodiesmentioning
confidence: 99%
“…At the end of the last century, Troyer et al ( 29 ) showed that a calorie-restricted diet was successful in modulating the key inflammatory ligand platelet-derived growth factor (PDGF) subunit A and the thrombin receptor, resulting in the suppression of murine lupus nephritis. Quite recently, the direct mechanism of this finding has been explained, elucidating the role of PDGF as a growth factor that regulates cell proliferation and is responsible for mesangial proliferation, periostin formation and progressive glomerulosclerosis ( 30 ).…”
Section: Macronutrientsmentioning
confidence: 99%